2021
DOI: 10.32615/ps.2021.029
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-dependent effects of fusaric acid on the photosynthetic activity of tomato plants

Abstract: yield in the dark-adapted state; FA -fusaric acid; FB1 -Fumonisin B1; FM -fresh mass; Fv/Fm -maximum quantum yield of PSII; HR -hypersensitive response; MDA -malondialdehyde; NPQ -nonphotochemical quenching; Nr -Never ripe; PCD -programmed cell death; qL -estimates the fraction of open PSII centres; qP -photochemical quenching; RC -reaction centres; ROS -reactive oxygen species; SA -salicylic acid; WT -wild type, Y(I) -effective quantum yield of PSI; Y(II) -effective quantum yield of PSII; Y(CEF) -yield of cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 99 publications
3
17
0
Order By: Relevance
“…This result suggests that these physiological processes are not dependent on the presence of active ET signaling in tomato plants under FB1 exposure. Similar results reported the rapid closure of stomata and reduced photosynthetic activity under FA exposure (Wu et al 2008;Singh et al 2017;Iqbal et al 2021b). Nevertheless, both water consumption efficacy and water uptake are closely linked with the size of stomatal aperture (Romero-Aranda et al 2001).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This result suggests that these physiological processes are not dependent on the presence of active ET signaling in tomato plants under FB1 exposure. Similar results reported the rapid closure of stomata and reduced photosynthetic activity under FA exposure (Wu et al 2008;Singh et al 2017;Iqbal et al 2021b). Nevertheless, both water consumption efficacy and water uptake are closely linked with the size of stomatal aperture (Romero-Aranda et al 2001).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the enhanced NPQ is considered as a good indicator for the induction of the photoprotective mechanisms which are mostly associated with the xanthophyll cycle and ΔpH formation in the thylakoid membranes (Miyake 2010;Zhang et al 2014). Our results depicted the enhanced NPQ in a concentration-dependent manner under FB1 exposure which was higher in WT than Nr plants under FB1 exposures after 72 h. Similar results were found upon exogenous application of another Fusarium toxin, fusaric acid (FA) to WT, and Nr tomato plants which resulted in the reduction of Y(II) and q P PSII parameters, while NPQ levels were elevated significantly (Iqbal et al 2021b). Furthermore, another study reported the role of ET on NPQ in eto1-1 and ctr1-3 mutants of Arabidopsis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Paired molecules of chlorophyll a absorb at 680 nm in the PSII, and at 700 nm in the PSI [88]. The decrease in the absorbance of red light, therefore, is a sign of a non-effective quantum yield of PSII and PSI [89], which in the initial stage of the wilting progression can be explained by the degradation of chlorophyll a and peroxidation of the thylacoid plasmalemma due to the photoprotective action of ethylene induced by exposure to F. oxysporum toxin, accompanied also by a significant reduction in stomatal conductance [90]. Indeed, this evidence is consistent with the results of previous research concerning chlorophyll-associated VIs that are highly correlated with F. oxysporum disease progression on Physalis peruviana L. [91], and on banana [92].…”
Section: Discussionmentioning
confidence: 99%